ANALISIS DAMPAK PEMBIAYAAN QARDUN HASAN TERHADAP KESEJAHTERAAN PEDAGANG DI ACEH - Damanhur Damanhur; Wahyudiah Utami (Faculty of Economics and Business, Universitas Malikussaleh, 2020)
The purpose of this study was to analyze the Impact of Qardun Hasan Financing on the Well-Being of Traders in the Lambaro Banda Aceh market. The data used in this study are primary data using sequential time data. The number of samples in this study were 34 members of the Banda Aceh Baitul Misyakat Sharia Cooperative whose receipts were traders in the Lambaro Banda Aceh market using accidental sampling techniques. Data obtained through interviews and questionnaires. The method of data analysis in this study used a paired t test method. The results of this study found that there was an impact on the welfare of traders as measured by religious activity, income, savings and alms. The four indicators showed an impact on the welfare of traders, this was concluded after looking at the conditions and data of traders before and after receiving Qardun Hasan's financing.